PERKAWINAN DENGAN PARIBAN PADA SUKU BATAK TOBA DI KOTA JAMBI - Sitanggang, Melati : Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Marriage is very important in Toba Batak Tribe community since it’s become the determination of the rights and obligations in community in order to maintain the lineage. This marriage serves as a bridge in implementing Dalihan Na Tolu customary system of the Toba Batak Tribe community. Ideal marriage for the Toba Batak community is a marriage with Pariban which is the tradition of matchmaking that has been carried out since long time ago until now even though this kind of marriage is a inbreeding marriage but still possible to happen. In Bataknese principles, Marga becomes the self-identity, if they have same clan from different descent they still considered as a relative, in other hand if they are Pariban the marriage is allowed since their clan are different although this marriage including to inbreeding marriages. The subjects of this study were 6 people from Raja Adat and people who married with their Pariban in Jambi City. The technique of determining the informants in this study is using purposive sampling technique. The research method used is descriptive qualitative research method. The theory used is the theory of Functionalism proposed by Malinowski. The results of the study can be concluded that Marriage with Pariban is an easier marriage as the determination of the dowry by marrying Pariban is not too difficult as what they wanted to, but the matchmaking tradition with Pariban has begun to disappear nowadays along with the development of technology and science. Keywords: Toba Batak Pariban Marriage, functionalism